Resiliency and Agility in Preventive and Corrective Maintenance by Optimization Approach - Karim Zadeh, Elham (International journal of industrial engineering and operational research, 2024)
Ensuring the uninterrupted operation of equipment and systems is critical across various industries. Preventive and corrective maintenance strategies play a vital role in achieving this goal. This paper explores how incorporating resiliency and agility principles into these maintenance processes, aided by optimization approaches, can significantly enhance overall equipment effectiveness. We delve into the concepts of preventive and corrective maintenance, highlighting the importance of both in maintaining system health. We then discuss how resiliency and agility can be fostered within these processes. The paper explores various optimization approaches, including data analytics, machine learning, and CMMS (Computerized Maintenance Management Systems), and their applications in optimizing maintenance tasks. We present a case study (to be populated with specific details in the Methodology section) to illustrate the implementation of these concepts and showcase the potential benefits. Finally, the paper concludes by summarizing the key takeaways and outlining potential future research directions.